2012
DOI: 10.1371/journal.pone.0049640
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Natural Variation in Oenological Traits in Saccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae is the main microorganism responsible for wine alcoholic fermentation. The oenological phenotypes resulting from fermentation, such as the production of acetic acid, glycerol, and residual sugar concentration are regulated by multiple genes and vary quantitatively between different strain backgrounds. With the aim of identifying the quantitative trait loci (QTLs) that regulate oenological phenotypes, we performed linkage analysis using three crosses between highly diverged S. cerevisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
78
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 62 publications
3
78
0
Order By: Relevance
“…We used the DBVPG6765 strain as representative of the WE lineage, YPS128 of the NA lineage, Y12 of the SA lineage, and DBVPG6044 of the WA one. These strains have been extensively characterized at the genomic (Liti et al 2009a) and phenotypic ) levels and successfully used for QTL mapping in two-parent crosses Parts et al 2011;Salinas et al 2012). To further improve the reference genomes, we resequenced the founders at high coverage and generated high-quality assemblies, containing .95% of the sequence for each strain in one large scaffold per chromosome (A. Bergström, J. T. Simpson, F. Salinas, L. Parts, A. Zia, A. N. Nguyen Ba, A. M. Moses, E. J. Louis, V. Mustonen, J. Warringer, R. Durbin, and G. Liti, unpublished results).…”
Section: Genetic Background Of Founder Strainsmentioning
confidence: 99%
“…We used the DBVPG6765 strain as representative of the WE lineage, YPS128 of the NA lineage, Y12 of the SA lineage, and DBVPG6044 of the WA one. These strains have been extensively characterized at the genomic (Liti et al 2009a) and phenotypic ) levels and successfully used for QTL mapping in two-parent crosses Parts et al 2011;Salinas et al 2012). To further improve the reference genomes, we resequenced the founders at high coverage and generated high-quality assemblies, containing .95% of the sequence for each strain in one large scaffold per chromosome (A. Bergström, J. T. Simpson, F. Salinas, L. Parts, A. Zia, A. N. Nguyen Ba, A. M. Moses, E. J. Louis, V. Mustonen, J. Warringer, R. Durbin, and G. Liti, unpublished results).…”
Section: Genetic Background Of Founder Strainsmentioning
confidence: 99%
“…For polygenic traits, it is called heterosis. Heterosis is commonly associated to macroscopic traits, but it also applies to less integrated traits such as metabolite abundances (3,4), fluxes and enzyme activities (5-7), mRNA, and protein amounts (8).…”
mentioning
confidence: 99%
“…cerevisiae has also been a focus for studies of natural genetic variation and polygenic traits (Liti and Louis 2012), as strains found in nature display a broad range of phenotypic variance (Ehrenreich et al 2009;Liti and Louis 2012). Studies of yeast strain natural variance have identified the causative alleles for a number of polygenic traits including sporulation efficiency (Deutschbauer and Davis 2005;Ben-Ari et al 2006;Gerke et al 2006), high temperature growth (Steinmetz et al 2002), translation efficiency (Torabi and Kruglyak 2011), and wine alcoholic fermentation (Salinas et al 2012). A major advantage of yeast in studies of natural variation caused by multiple mutations is the ability to perform allele replacements, allowing direct tests for causative mutations.…”
mentioning
confidence: 99%